Elizabeth Rees, Archaeology and the Early Church in Southern Greece. - Tzavella, Elli (Journal of Greek Archaeology, 2025)
The main value of the book is the inclusion of selected textual, topographic and archaeological information, organized by geographic region. Thus, the reader can easily follow an itinerary around the most important archaeological sites of the Northeastern Peloponnese, and Athens. While the aim of the book is to be lauded, the archaeological evidence included has been presented very selectively, and through a rather uncritical lens. The significant and on-going academic discussions around regional chronology, archaeological methodology, and factors which may have influenced the spread of early Christianity in Greece are absent in this work.